'How Writers Work': Interviewing the Author in Everyman. Issue 4 (6th June 2016) - Roach, Rebecca
Abstract : Drawing on the archives of publishers and individuals, this article analyses the space of the study and the marketplace in a series of interviews by American journalist Louise Morgan, published in the London-based middlebrow Everyman magazine in the early 1930s. A form largely unstudied by literary scholars, the interview offers an important space for exploring issues of publicity and privacy, representations of literary labour and the profession of authorship in this period . In the moment before Q.D. Leavis published Fiction and the Reading Public, before literary studies began to be institutionalised, before New Critical distaste for authorial intention, personae and study of the marketplace largely excluded the interview and the middlebrow from critical study, Morgan's series offers a productive site from which to consider the space of production, the marketplace and, indeed, the work of writing itself.